Republic of Sudan Diagnostic Trade Integration Study Update : Reducing Trade Costs to Increase Competitiveness and Rresilience - World Bank Group (World Bank, Washington, DC, 2015)
The Diagnostic Trade Integration Study (DTIS) update identifies priority actions in support of the Government of Sudan (GOS) commitment to increase trade and diversify the economy. The current study builds on the earlier 2008 DTIS by identifying the major factors holding back the increase of agricultural exports and economic diversification. The report identifies a package of measures that will support Sudan to more effectively realize its economic potential. The DTIS Update presents an updated action matrix that summarizes the recommended policy reforms. This matrix was validated with a wide variety of stakeholders in Khartoum in September 2014. Together, the action points will contribute to reducing trade costs, thereby enabling Sudanese enterprises and farmers to compete more successfully in regional and global markets and realize the GOS objectives of expanding and diversifying exports for increased economic growth. The recommendations accept that any changes in tariff schedules should be ‘revenue neutral,’ given the existing challenging fiscal situation.